138k views
4 votes
If f(x) = -5x -9 then f^-1(x) = ____

2 Answers

6 votes

Answer:

f⁻¹(x) = -(x+9) / 5

Explanation:

We have given a function.

f(x) = -5x -9

We have to find inverse of given function.

Let y = f(x)

y = -5x-9

Solving above equation for x, we have

x = -(y+9) / 5

Putting x = f⁻¹(y) in above equation ,we have

f⁻¹(y) = -(y+9) / 5

Replacing y by x, we have

f⁻¹(x) = -(x+9) / 5 which is the answer.

User Ahmed Ibrahim
by
4.6k points
4 votes

Answer:


f^(-1)(x)=-(x+9)/(5);

Explanation:

The given linear function is;


f(x)=-5x-9

Let
y=-5x-9;

Interchange
x and
y to get;


x=-5y-9;

Solve for
y.


x+9=-5y

Divide both sides by -5


(x+9)/(-5)=y;

This implies that;


f^(-1)(x)=-(x+9)/(5);

User Sotiris Kiritsis
by
4.7k points